If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + 6) + -1(4 + 3y) = 12 Reorder the terms: (6 + 4y) + -1(4 + 3y) = 12 Remove parenthesis around (6 + 4y) 6 + 4y + -1(4 + 3y) = 12 6 + 4y + (4 * -1 + 3y * -1) = 12 6 + 4y + (-4 + -3y) = 12 Reorder the terms: 6 + -4 + 4y + -3y = 12 Combine like terms: 6 + -4 = 2 2 + 4y + -3y = 12 Combine like terms: 4y + -3y = 1y 2 + 1y = 12 Solving 2 + 1y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1y = 12 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = 12 + -2 1y = 12 + -2 Combine like terms: 12 + -2 = 10 1y = 10 Divide each side by '1'. y = 10 Simplifying y = 10
| x+(0.15x)=300 | | 46(2x-3)=8-2(3x+1) | | 5-x=12x+4 | | 5m+1-1m=1+4m | | -3x-35=-8x | | 3x=10y+13 | | -3x=-126 | | x^2+4y-51=0 | | -2(y+6)=-2(g+31) | | 6v-20=8v | | 9-4(7x-8x)=x-43 | | -.3(x+6)=-2.4(x-1) | | -6(1-2x)=2+8x | | 1.75x-3.5=-.875x-.25 | | 3c-7d=-1 | | 12-a-3a=4a-4a | | 12y-6-4y-6-2y+3= | | 7x+10=-46 | | 20x^2-45x=0 | | -8(8-x)-3x=14-8x | | 3x-4cos(x+2)=0 | | 4m^2+12m+5= | | x-5/2-1=x-p/3 | | 4cos(x+2)-3x=0 | | 9x+5x-5+12x+15+15x-60=360 | | -9x+7=3x+119 | | .61x-.75=-2.5(x+1.5) | | 3y+6x+18=0 | | 2sin(x)+3= | | .61y-.75=-2.5(y+1.5) | | -9t-81+2t=8+t | | 1.5(35)b=140 |